Pendampingan Pengelolaan Sampah Berkelanjutan melalui Ecobrick, Ecoprint, dan Bank Sampah - Ansori, Arif; Al Haq, Abdul Aziz; Suryadi, Muhammad Abrar; Alfayed, Erico; Lestari, Sri Ayu; Ningsih, Nurwidia; Intan, Melani Nur; Fadila, Sovie; Rambe, Multisari; Masyhur, Laila Sari (MENARA RIAU, 2025)
This community service program aimed to address waste management issues through the implementation of ecobrick, ecoprint, and waste bank initiatives. The ecobrick program successfully reduced plastic waste by involving students in creating eco-friendly bricks used to build the village name sign. The ecoprint program, targeting local women's groups (PKK), enhanced their skills in transforming organic waste into valuable artistic products such as leaf-patterned tote bags. Meanwhile, the establishment of a waste bank encouraged residents to sort organic and inorganic waste and promoted collective participation in sustainable waste management. These three programs not only helped reduce environmental pollution but also created new economic opportunities for the community. The results showed increased awareness and engagement among residents in sustainable waste practices, aligning with environmental development goals and community empowerment efforts.